Experiences of people with epilepsy on the use of digital services - Reinikainen, Niina; Jylhä, Virpi; Rosenlund, Milla (Finnish Journal of eHealth and eWelfare, 2024)
Digital health services have enabled the production of health data and up-to-date monitoring, and have increased interaction between citizens and health care during the treatment process. The purpose of this study was to describe the experiences of people with epilepsy in the use of health services and to find out what kind of development measures increase the citizen's involvement in the use of digital health services. The study was conducted as three focus group interviews for people with epilepsy (N=8) between December 2022 and March 2023. The interviews were recorded, and the material transcribed according to a secure practice. The transcripts were analyzed using inductive content analysis using Atlas.ti software (version 23). As a rule, digital health services were perceived as easy to use and accessible. Producing and communicating personal health information to healthcare professionals was considered important, as they were seen to promote health and improve the efficiency and quality of care. Health information was communicated to health care personnel using pre-information forms and symptom diaries, while interaction was mainly carried out in the form of messages. Re-requests for prescriptions through the Kanta service seemed to have become an established practice. In addition, information obtained through well-being devices, such as smartwatches and rings, was sometimes stored in the National Kanta Service's Personal Data Repository. Health services provided by health care organizations showed differences within organizations. The interviewees felt that utilizing their own health data during a visit to the clinic brings added value in monitoring the patient's overall health and care. However, health care professionals make use of digital health services on different levels, which may have left the available information untapped. The development needs for the usability of digital health services were mentioned to improve the smoothness of logging in and recording information. In addition, to improve availability, there should be one transaction channel covering digital services.